Are we ready? Preparedness of acute care providers for the Rugby World Cup 2011 in New Zealand. Issue 8 (1st November 2011) - Al-Shaqsi, Sultan; McBride, David; Gauld, Robin; Al-Kashmiri, Ammar; Al-Harthy, Abdullah
Abstract : New Zealand is hosting the Rugby World Cup (RWC) 2011. It is the largest sporting event in New Zealand's history, with around 70 000 fans estimated to visit the country from September to October 2011. This influx of tourists will have an impact on its already stretched healthcare services. The preparedness of New Zealand's healthcare system to handle this mass event is unclear. Objectives: The two main objectives of this study were (1) to determine the perceived preparedness of acute care providers in New Zealand to respond to the healthcare demands of RWC 2011; and (2) to determine the factors associated with perceived strong preparedness among acute care providers in New Zealand. Method: A cross-sectional survey of 1500 doctors, nurses and ambulance officers working in acute care services in New Zealand was conducted between June 2010 and March 2011. Results: 911 surveys were completed (response rate 60.7%). Only 12.7% of acute care providers felt they were prepared to deal with possible health issues arising from RWC 2011. Perceived preparedness was highest among ambulance officers and lowest among providers in intensive care units (16.3% vs 4.1%, p<0.01). Acute care providers who were aware of their role in a mass emergency were more likely to report preparedness with a prevalence OR of 3.5 and a 95% CI of 2.1 to 5.7. Conclusion: Only 12.7% of acute care providers in New Zealand perceived preparedness for RWC 2011. Perceived preparedness followed a stepwise decline from prehospital services, emergency department, to surgery and then finally to intensive care services. This indicates that current preparedness activities are focusing on prehospital emergency services and neglecting surgical and intensive care services. Awareness about the role of acute care providers during emergencies, training and previous experience were associated with perceived strong preparedness for RWC 2011.